Characterization of Physicochemical Properties and IgE‐Binding of Soybean Proteins Derived from the HHP‐Treated Seeds. Issue 11 (11th October 2014) - Yang, Hui; Yang, Anshu; Gao, Jinyan; Chen, Hongbing
Abstract The aim of this work was to evaluate the characterization of physicochemical properties and IgE‐binding of soybean proteins derived from the high hydrostatic pressure (HHP) treated seeds. Soybean seeds were treated by HHP at different pressures, and changes in the physicochemical properties of soybean proteins were characterized by proteins solubility, free sulfhydryl (SH) content, surface hydrophobicity, and secondary structures. Sodium dodecyl sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and enzyme‐linked immunoabsorbent assay (ELISA) were used to define the proteins patterns and IgE‐binding ability. The results showed that HHP treatment in the ranges of 0 to 500 MPa led to a slight but gradual decline in free SH content. The solubility and hydrophobicity of soybean proteins increased sharply from 100 to 200 MPa, and gradually decreased upon the further increase of pressure. The α‐helix and β‐sheets contents of soybean proteins decreased, while the random coil content increased. The SDS‐PAGE showed that HHP treatment of 100 to 200 MPa could dissociate the proteins, breaking the aggregates into smaller units, while the treatment ranging from 300 to 500 MPa could induce the proteins aggregation into larger units. Moreover, the ELISA revealed that the IgE‐binding of soybean proteins after HHP treatment at 200 MPa decreased 61.7% compared to the untreated group. Our findings suggested that HHP processing could not only modify the physicochemical properties of soybean proteins, but also significantly reduce its IgE‐binding at an appropriate pressure level.